Endogenous Cushing's Syndrome with Precocious Puberty in an 8-Year-Old Boy due to a Large Unilateral Adrenal Adenoma. (4th March 2013) - Hossain, Muhammad Rajib; Alam, Md. Mashiul; Nabi, Junaid; Kibria, Mahzabin
Abstract : Adrenocortical tumors (ACTs) causing Cushing's syndrome are extremely rare in children and adolescents. Bilateral macronodular adrenocortical disease which is a component of the McCune-Albright syndrome is the most common cause of endogenous Cushing's syndrome. We report the case of a boy with Cushing's syndrome who presented with obesity and growth retardation. The child was hypertensive. The biochemical evaluation revealed that his serum cortisol levels were 25.80 μ g/dL, with a concomitant plasma ACTH level of 10.0 pg/mL and nonsuppressed serum cortisol on high-dose dexamethasone suppression test (HDDST) to be 20.38 μ g/dL. Computed tomography of the abdomen demonstrated a 8 × 6 × 5 cm left adrenal mass with internal calcifications. Following preoperative stabilization, laparotomy was carried out which revealed a lobulated left adrenal mass with intact capsule weighing 120 grams. Histopathological examination revealed a benign cortical neoplastic lesion, suggestive of adrenal adenoma; composed of large polygonal cells with centrally placed nuclei and prominent nucleoli without capsular and vascular invasion. On the seventh postoperative day, cortisol levels were within normal range indicating biochemical remission of Cushing's syndrome. On followup after three months, the patient showed significant clinical improvement and had lost moderate amount of weight and adrenal imaging was found to be normal.